2022
DOI: 10.52965/001c.38243
|View full text |Cite
|
Sign up to set email alerts
|

Opioids in Urology: How Well Are We Preventing Opioid Dependence and How Can We Do Better?

Abstract: Urologic procedures (both open and minimally invasive) can cause pain due to the surgery itself, devices placed, and post-operative issues. Thus, pain management is important for every post-procedure recovery period. Opioid use post-surgery is common and often over-prescribed contributing to persistent use by patients. In this article, we review the extent of opioid use in pediatric urologic procedures, vasectomy, endourologic procedures, penile implantation, urogynecologic procedures, prostatectomy, nephrecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…This is in contrast to prior literature in which surgical type and approach were both associated with differences in opioid prescription. 8,17,24 Okoro et al found that patients undergoing open surgery for kidney cancer were more likely to receive higher doses of opioids. 18 However, we hypothesize that patients undergoing open surgery had a longer hospital recovery with inpatient opioids; these patients are more likely to have achieved pain control at discharge, resulting in a comparable opioid-free discharge rate compared to patients with minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to prior literature in which surgical type and approach were both associated with differences in opioid prescription. 8,17,24 Okoro et al found that patients undergoing open surgery for kidney cancer were more likely to receive higher doses of opioids. 18 However, we hypothesize that patients undergoing open surgery had a longer hospital recovery with inpatient opioids; these patients are more likely to have achieved pain control at discharge, resulting in a comparable opioid-free discharge rate compared to patients with minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Lack of standardization and variation in prescribing patterns has the potential to lead to overprescribing; prior literature establishes that up to 77% of prescribed options go unused following prostate and kidney surgery. [7][8][9] Additionally, surgical specialties continue to lack formal training on pain management, perpetuating a cycle for physicians in training. 10 Opioid-free discharge has been shown to be safe and feasible for a variety of urologic procedures.…”
mentioning
confidence: 99%
“…Historical pain regimens have relied heavily on opioid medications. Given the potential risk for adverse use, abuse, and dependence, it is imperative that urologic surgeons focus on non-opioid interventions to minimize the need for opioids ( 41 ). Multi-modal approaches that include administration of local anesthetic blocks intraoperatively coupled with oral anti-inflammatories and neuropathic pain agents can dramatically reduce the need for opioids after PP placement ( 42 ).…”
Section: Postoperative Considerationsmentioning
confidence: 99%